Small rubber particle proteins from Taraxacum brevicorniculatum promote stress tolerance and influence the size and distribution of lipid droplets and artificial poly(cis‐1, 4‐isoprene) bodies. (1st March 2018) - Laibach, Natalie; Schmidl, Sina; Müller, Boje; Bergmann, Maike; Prüfer, Dirk; Schulze Gronover, Christian
Summary: Natural rubber biosynthesis occurs on rubber particles, i.e. organelles resembling small lipid droplets localized in the laticifers of latex‐containing plant species, such as Hevea brasiliensis and Taraxacum brevicorniculatum . The latter expresses five small rubber particle protein (SRPP) isoforms named TbSRPP1–5, the most abundant proteins in rubber particles. These proteins maintain particle stability and are therefore necessary for rubber biosynthesis. TbSRPP1–5 were transiently expressed in Nicotiana benthamiana protoplasts and the proteins were found to be localized on lipid droplets and in the endoplasmic reticulum, with TbSRPP1 and TbSRPP3 also present in the cytosol. Bimolecular fluorescence complementation confirmed pairwise interactions between all proteins except TbSRPP2. The corresponding genes showed diverse expression profiles in young T . brevicorniculatum plants exposed to abiotic stress, and all except TbSRPP4 and TbSRPP5 were upregulated. Young Arabidopsis thaliana plants that overexpressed TbSRPP2 and TbSRPP3 tolerated drought stress better than wild‐type plants. Furthermore, we used rubber particle extracts and standards to investigate the affinity of the TbSRPPs for different phospholipids, revealing a preference for negatively charged head groups and 18:2/16:0 fatty acid chains. This finding may explain the effect of TbSRPP3–5 on the dispersity of artificial poly( cis ‐1, 4‐isoprene) bodies and on the lipid droplet distribution we observed in N . benthamiana leaves. Our data provide insight into the assembly of TbSRPPs on rubber particles, their role in rubber particle structure, and the link between rubber biosynthesis and lipid droplet‐associated stress responses, suggesting that SRPPs form the basis of evolutionarily conserved intracellular complexes in plants. Significance Statement: Small rubber particle proteins (SRPPs) promote rubber particle stability and rubber biosynthesis although they are related to proteins involved in stress responses and lipid droplet organization. We provide insight into the assembly of SRPPs in rubber particles, their structural role in the organization of these organelles, and the link between rubber biosynthesis and lipid droplet‐associated stress responses. Our data indicate that SRPPs arise from evolutionarily conserved stress‐related proteins, and that they stabilize lipid droplets and influence their number and size. This process is mediated by specific interactions between SRPPs and the phospholipid membrane on the particle or droplet surface.